2021
DOI: 10.3389/fgene.2021.738879
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Selective Scans Detect Genes Associated With Important Phenotypic Traits in Sheep (Ovis aries)

Abstract: Sheep (Ovis aries) is one of the important livestock with diverse phenotypic traits. However, little is known about the molecular mechanism of diverse phenotypic traits in domestic sheep. Using the genome-wide high-density SNP data (600K) in 253 samples from 13 populations, we conducted the tests of selective sweeps (i.e., pairwise FST and XP-CLR) associated with several important phenotypic traits (e.g., tail types, horn morphology, prolificacy, coat pigmentation, ear size, milk production, meat production, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
0
12
0
1
Order By: Relevance
“…SNPs identified in this region include FAM110B, UBXN2B, LOC101116841, SDCBP, and NSMAF. It has been reported that these SNPs are associated with meat and carcass traits such as adiposity, sensory and anatomical characteristics (Lee et al 2013;Li & Kim 2015;Li et al 2017;Hay & Roberts 2018;de las Heras-Saldana et al 2020;Naserkheil et al 2020;Srikanth et al 2020;Srivastava et al 2020;Takeda et al 2020;Naserkheil et al 2021;Xu et al 2021;Fonseca et al 2022); health traits such as resistance to temperature stress, mastitis, and diseases (Kommadath et al 2014;Chen et al 2015;Minuti et al 2015;Smith et al 2019;Deng et al 2020;Li et al 2020;Naserkheil et al 2020;Brunes et al 2021;Londoño-Gil et al 2021;Ruan et al 2021;Haire et al 2022); production traits such as growth, feed intake, and feed conversion (Weng et al 2016;Seabury et al 2017); reproductive traits such as female fertility and age at calving (Fortes et al 2012;Gaddis et al 2017;Mota et al 2017;Silva et al 2020;Oliveira et al 2021;Fonseca et al 2022) and appearance traits such as coat color (Senczuk et al 2020;Chhotaray et al 2021). Genomic regions and genes identified as under selection using iHS and ROH approaches have been associated with various ecological and economic traits in studies conducted on livestock.…”
Section: Discussionmentioning
confidence: 99%
“…SNPs identified in this region include FAM110B, UBXN2B, LOC101116841, SDCBP, and NSMAF. It has been reported that these SNPs are associated with meat and carcass traits such as adiposity, sensory and anatomical characteristics (Lee et al 2013;Li & Kim 2015;Li et al 2017;Hay & Roberts 2018;de las Heras-Saldana et al 2020;Naserkheil et al 2020;Srikanth et al 2020;Srivastava et al 2020;Takeda et al 2020;Naserkheil et al 2021;Xu et al 2021;Fonseca et al 2022); health traits such as resistance to temperature stress, mastitis, and diseases (Kommadath et al 2014;Chen et al 2015;Minuti et al 2015;Smith et al 2019;Deng et al 2020;Li et al 2020;Naserkheil et al 2020;Brunes et al 2021;Londoño-Gil et al 2021;Ruan et al 2021;Haire et al 2022); production traits such as growth, feed intake, and feed conversion (Weng et al 2016;Seabury et al 2017); reproductive traits such as female fertility and age at calving (Fortes et al 2012;Gaddis et al 2017;Mota et al 2017;Silva et al 2020;Oliveira et al 2021;Fonseca et al 2022) and appearance traits such as coat color (Senczuk et al 2020;Chhotaray et al 2021). Genomic regions and genes identified as under selection using iHS and ROH approaches have been associated with various ecological and economic traits in studies conducted on livestock.…”
Section: Discussionmentioning
confidence: 99%
“…From these findings and discussions, it can be concluded that RGS20, TCEA1, LYPLA1, MRPL15 , and EIF5 genes are strongly associated with carcass weight in Hawai’i beef cattle. Additionally, MYCT1 and CERS6 are possibly candidate genes for carcass weight in cattle, as their roles have been identified in pigs and sheep ( Wu et al, 2020 ; Xu et al, 2021 ). Further studies are required to ascertain the association of MYCT1 and CERS6 genes with carcass weight and to better understand their biological roles in cattle.…”
Section: Discussionmentioning
confidence: 99%
“…KEGG analysis further validated SCD5 ’s role in fatty acid metabolism and the biosynthesis of unsaturated fatty acids but added the AMPK signaling pathway. A recent study implemented whole-genome tests for various economically important traits in sheep and suggested SCD5 as a strong candidate for body size [ 54 ]. Given that SCD5 was previously proposed to partake in the body size development of grass-fed Brangus steers [ 55 ], there is support for this gene as a strong candidate involved in sheep growth.…”
Section: Discussionmentioning
confidence: 99%